Penggunaan Media Sosial dalam Membangun Moderasi Beragama di Masa Pandemi Covid-19 di Kota Tangerang - Novia, Washilatun; Wasehudin, Wasehudin (Hanifiya: Jurnal Studi Agama-Agama, 2020)
This article reflects diversity during the Covid-19 pandemic in Tangerang City. The Covid-19 Pandemic period requires all activities to be carried out online. This makes the use of social media unavoidable. This study used a descriptive qualitative method with observation and interviews as a technique used for data collection. The results of the study reveal that the active and massive use of social media to exchange information causes a wise attitude in dealing with the information received is needed. An attitude of wisdom, moderation, tolerance, and fairness is a reflection of moderation. The widespread use of social media and used as the main tool for activities, has made social media an educational tool for religious moderation. Parties such as religious leaders, educators, public figures, or even the public can spread the notion of religious moderation to the public through their respective activities, some of which include studies and lectures, millennial educational content, and educational comics on social media. This study recommends that parties involved in the world of education and propagation can instill an understanding of religious moderation with various media, including social media.